Pentamethine cyanine dyes with alkynyl group as perspective structure for conjugation with targeting moiety - Uspenskaia, Anastasiia A.; Doroshenko, Irina A.; Popovicheva, Kseniia A.; Shmychkov, Nazar V.; Pryakhina, Ekaterina V.; Shafikov, Radik R.; Skvortsov, Dmitrii A.; Beklemishev, Mikhail K.; Zaborova, Olga V.; Podrugina, Tatiana A.; Machulkin, Aleksei E.; Beloglazkina, Elena K. (Bioorganic & medicinal chemistry letters, 2025)
[Display omitted] •An asymmetric carbocyanine for the [3+2] cycloaddition reaction was obtained.•A triazole ring does not affect the photophysical properties of the fluorophore.•The conjugation to the vector molecule does not abolish the selective binding. We report a modified carbocyanine-based asymmetric fluorescent dye, suitable for the azide-alkyne cycloaddition reaction, that possesses promising photochemical properties (Φfl = 0,49). As an example of usage of the new fluorophore, it was conjugated to a ligand targeting prostate-specific membrane antigen (PSMA), one of the widely utilized prostate cancer markers.